Mobility of BtuB and OmpF in the Escherichia coli Outer Membrane: Implications for Dynamic Formation of a Translocon Complex - Spector, Jeff (The Biophysical Society, 2010)
Diffusion of two Escherichia coli outer membrane proteins—the cobalamin (vitamin B12) receptor (BtuB) and the OmpF porin, which are implicated in the cellular import pathways of colicins and phages—was measured in vivo. The lateral mobility of these proteins is relevant to the mechanism of formation of the translocon for cellular import of colicins such as the rRNase colicin E3. The diffusion coefficient (D) of BtuB, the primary colicin receptor, complexed to fluorescent antibody or colicin, is 0.05 ± 0.01 μm(2)/s and 0.10 ± 0.02 μm(2)/s, respectively, over a timescale of 25–150 ms. Mutagenesis of the BtuB TonB box, which eliminates or significantly weakens the interaction between BtuB and the TonB energy-transducing protein that is anchored in the cytoplasmic membrane, resulted in a fivefold larger value of D, 0.27 ± 0.06 μm(2)/s for antibody-labeled BtuB, indicating a cytoskeletal-like interaction of TonB with BtuB. OmpF has a diffusion coefficient of 0.006 ± 0.002 μm(2)/s, ∼10-fold smaller than that of BtuB, and is restricted within a domain of diameter 100 nm, showing it to be relatively immobile compared to BtuB. Thus, formation of the outer membrane translocon for cellular import of the nuclease colicins is a demonstrably dynamic process, because it depends on lateral diffusion of BtuB and collisional interaction with relatively immobile OmpF.